2013
DOI: 10.1007/s10029-013-1075-x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of post-operative instructions after inguinal hernia repair in England in 2012

Abstract: Surgeons and trusts should be able to provide patients with printed consistent and accurate information regarding their post-operative recovery time, including return to driving and return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Studies have also shown a wide range of advice being given following non‐obstetric and gynaecological surgery. A wide range of timeframes regarding resumption of driving were found in patient information leaflets after hernia repair in England (24 h to six weeks) and returning to work (one to six weeks) . This was not consistent with the Royal College of Surgeons patient information leaflet which suggests that patients wait for at least a week after surgery before resuming driving .…”
Section: Discussionmentioning
confidence: 84%
“…Studies have also shown a wide range of advice being given following non‐obstetric and gynaecological surgery. A wide range of timeframes regarding resumption of driving were found in patient information leaflets after hernia repair in England (24 h to six weeks) and returning to work (one to six weeks) . This was not consistent with the Royal College of Surgeons patient information leaflet which suggests that patients wait for at least a week after surgery before resuming driving .…”
Section: Discussionmentioning
confidence: 84%
“…The authors affirmed that the peritoneal incision and closure with continuous suture may be responsible for high pain scores for TAPP repair. However, not only the peritoneal incision is determinant of postoperative pain, but also several factors including patients' subjective pain perception and expression, different protocols for anesthesia, postoperative analgesia, methods for mesh fixation (tacks vs. glue vs. self-gripping), mesh type, and weight (g/m 2 ) have been shown to be additional causes of postoperative pain [56][57][58][59]. While our results seem to support equivalent Surgeon experience, expertise, variation in technical skills, and hospital volume are key determinants for operative time while TAPP and TEP have been shown to be associated with a steep learning curve [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The provision of written information leaflets may contribute to patient understanding, and reduce claims relating to a lack of information and poor communication skills 26 . Written information is not without its limitations however, and has been shown to vary widely in terms of quality and in evidence base 28 30 . A Cochrane review of the use of decision aids, including leaflets but also multimedia options (such as video and online interactive tools), found that they were effective in informing patients of realistic outcomes and complications; however, the review found no studies on the effect of decision aids on litigation 31 .…”
Section: Discussionmentioning
confidence: 99%